Dirtmeister's nitty gritty planet Earth : all about rocks, minerals, fossils, earthquakes, volcanoes, and even dirt! - Tomecek, Steve (Washington, D.C. : National Geographic Society, 2015)
"Come and explore the world under your feet with the Dirtmeister and friends! Part graphic novel, part fun guidebook, this very cool, rocky journey introduces both eager and reluctant readers to the basic geologic processes that shape our Earth. Clear and concise explanations of the various geologic processes reveal the comprehensive science behind each fascinating topic. Fun facts and simple DIY experiments reinforce the concepts while short biographies of important scientists inspire future geo-scientists"--Publisher.
How it all began -- Magnificent minerals -- Earthquakes and their origins -- Fire down below -- Shifting plates and drifting continents -- What goes up must come down -- The rock cycle -- Digging old dead things -- The dynamics of dirt -- Rockin' resources -- Stem science standards.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references and index.
8-12.
Description based on print version record.
Keywords: Geology -- Juvenile literature; Geology; Geology; Electronic books- OSLIS; Children's nonfiction; Juvenile works; Electronic books